A Study on the Influencing Factors of Teaching Interaction on Deep Learning from the Perspective of Social Cognitive Theory (Global Journal of Human-Social Science, 2022)
Based on Social Cognitive Theory SCT a research model is constructed with teaching interaction as the independent variable self-efficacy as the mediating variable and Deep learning as the dependent variable The research uses regression analysis and Bootstrap test to explore the impact of teaching interaction on college students Deep learning and the mediating role of self-efficacy The research results show that teaching interaction positively and significantly affects college students Deep learning and self- efficacy of which material-chemical interaction has the most significant effect on college students Deep learning 0 431 self-efficacy positively affects college students Deep learning 0 255 and play a partial mediating role in teaching interaction and Deep learning Finally the research proposes to build a multi-modal interaction mechanism to promote the realization of Deep learning to create an embodied collaborative learning context to improve the quality of teaching interaction Learn and reference